Proceedings of the 2016 5th International Conference on Environment, Materials, Chemistry and Power Electronics 2016
DOI: 10.2991/emcpe-16.2016.156
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of antioxidant and anticancer of the extracts from Various Habitats of Selaginella doederleinii

Abstract: Abstract. In this study, aioxidant and anticancer activities of the extracts were evaluated from various habitats of Selaginella doederleinii. The evaluation on antioxidative capacity revealed that the extracts were the highest from Guizhou province using DPPH radical scavenging, ABTS radical scavenging, ferric reducing and FRAP methods, while those of the extracts from Sichuan province were the lowest from different habitats. The evaluation on antitumous effect showed that the extracts from Guizhou province w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
2

Year Published

2018
2018
2019
2019

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 12 publications
0
1
0
2
Order By: Relevance
“…However, the extraction efficiency was constantly decreased with the further increasing of the ratios of liquid to raw material. The possible reason was that an excess solvent to solid ratio could produce a lot of impurities [33], and cause a significant reduction of TBF content. This indicated that a proper solid–liquid ratio was enough for the extraction.…”
Section: Resultsmentioning
confidence: 99%
“…However, the extraction efficiency was constantly decreased with the further increasing of the ratios of liquid to raw material. The possible reason was that an excess solvent to solid ratio could produce a lot of impurities [33], and cause a significant reduction of TBF content. This indicated that a proper solid–liquid ratio was enough for the extraction.…”
Section: Resultsmentioning
confidence: 99%
“…Ekstrak etil asetat dari Selaginella doederleinii Hieron juga berpotensi sebagai sumber bioaktif alami yang mudah didapat dari alam. Aktivitas ekstrak tersebut dikaitkan dengan kandungan fenoliknya, terutama amenoflavon, hinokiflavon dan robustaflavon (Gang et al 2016).…”
Section: Antioksidanunclassified
“…Zat bioaktif utama ekstrak Selaginella doederleinii Hieron sebagian besar bersifat fenolik. Amentoflavon tidak hanya dapat secara efektif menghambat berbagai macam proliferasi sel tumor tetapi juga menginduksi apoptosis sel tumor dan diferensiasi (Gang et al 2016). Di sisi lain, ekstrak etanol Selaginella doederleinii Hieron menunjukkan aktivitas penghambatan yang berbanding lurus dengan konsentrasi pada sel CNE-1, sementara tidak menunjukkan kecenderungan proporsional yang jelas sehubungan dengan sel C666-1 (Lian et al 2013).…”
Section: Antitumorunclassified